PERSEPSI MAHASISWA TENTANG KETIDAK-JUJURANAKADEMIK: STUDI KASUS MAHASISWA PROGRAM VOKASI UNIVERSITAS INDONESIA - Yuliyanto, Heri (UI Scholars Hub, 2015)
Often we see students gathered tasks given by the lecturers and they are copying answers between students and others. They perform this action with no load, even though the task is an individual task. Do they know that what they are doing is an action that is contrary to the basic values of academic integrity. Or perhaps they are not aware that they are not a violation, since they merely imitate or follow the habits of seniors or friends the same age. Then comes the question